Penerapan Strategi Pembelajaran dengan Aplikasi Orbit Mind-Mind Mapping untuk Meningkatkan Hasil Belajar Part Of Speech Mahasiswa Vokasi Universitas Serang Raya - Ratu Dea Mada Badriyah Mada Badriyah; Marlia Purnamasari; Wahyu Fadillah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research intends to describe the actions of lecturers and students during the learning process and the consequences of student learning when mind mapping learning methodologies are used using the Orbit Mind Mapping application. This study utilized a three-cycle class action research method. Observations, cognitive tests, and questionnaires regarding student responses to learning methodologies utilizing the Orbit Mind Mapping application provided the research data. From the results of the questionnaire, it was determined that students preferred or agreed with the use of the orbit mind mapping application, that students tended to be more creative when using the Orbit Mind Mapping application, and that there was an increase in the results of cognitive tests, with an average score of 42,6 in the first cycle, 53.9 in the second cycle, and 80.4, respectively. Thus, it may be stated that the Orbit Mind Mapping program increases student learning results in part of speech material. For future study, it is proposed to employ methods other than classroom action research, and this application can be implemented in classes outside English.